Türk anayasa mahkemesi kararlarında çocuğun anayasal statüsü - Gümüş, Canberk (My University, 2023)
Çocuğun korunması dünyada sosyal devlet anlayışının gelişmesiyle paralel olarak bütün devletlerin meselesi haline gelmiştir. Bütüncül ve sistemli olarak, özgülenmiş şekilde çocuk haklarını ele alan bağlayıcı niteliğe sahip ilk uluslararası belge olan 1989 Birleşmiş Milletler Çocuk Hakları Sözleşmesi Türkiye tarafından imzalanmış ve gerekli usuller yerine getirilerek Türk hukukunda yürürlüğe girmesi sağlanmıştır. Türkiye’nin Birleşmiş Milletler Çocuk Hakları Sözleşmesi’ne taraf olması, Türk hukukunda toplum ve özellikle aile ilişkilerinde köklü bir değişiklik olarak 2001’de Türk Medeni Kanunu’nun kabul edilmesi, 1982 Anayasası’nın çocukları da ilgilendiren bazı hükümlerinde 2010 yılında değişiklikler yapılması gibi olgular Yüksek Mahkemenin içtihadına etki etmiştir. Mahkeme, Anayasa’yı ve özellikle Birleşmiş Milletler Çocuk Hakları Sözleşmesi’ni yorumlayıp uygularken kimi zaman isabetli kimi zaman isabetsiz yöntemler uygulamıştır. Anayasa Mahkemesinin çocukla ilgili meselelerde oluşturacağı belirli ve kapsamlı bir içtihat, Devletin yükümlülüklerini hayata geçirmek için gerekli normları oluşturmada kanun koyucuya, bu normların uygulanmasında Devletin diğer organlarına yol gösterecektir ve çocukların uluslararası seviyeye uygun belli bir anayasal statüye kavuşmasında rol oynayacaktır.

The protection of the child has become a matter of all states in parallel with the development of the social state understanding in the world. The 1989 United Nations Convention on the Rights of the Child, which is the first international document with a binding nature that specifically and specifically addresses children's rights in a holistic and systematic manner, was signed by Turkey and entered into force in Turkish law by following the necessary procedures. Facts such as becoming a party to the United Nations Convention on the Rights of the Child, adoption of the Turkish Civil Code in 2001 as a radical change in Turkish law in society and especially in family relations, amendments to some of the provisions of the 1982 Constitution, which also concern children, in 2010 affected the Constitutional Court’s jurisprudence. While interpreting and applying the Constitution and especially the United Nations Convention on the Rights of the Child, the Court applied sometimes correct and sometimes incorrect methods. A clear and comprehensive jurisprudence to be established by the Constitutional Court in matters related to children guides the legislator on the creation of the necessary norms to fulfill the obligations of the State, and the other organs of the State on the implementation of these norms, and plays a role on the attainment of a certain constitutional status in accordance with the international level of children.
The constitutional status of the child in the decisions of the Turkish constitutional court
Keywords: best interests of the child; Birleşmiş Milletler Çocuk Hakları Sözleşmesi Turkish Constitutional Court; children's rights; çocuğun korunması; çocuğun üstün yararı; çocuk hakları; Kamu hukuku; protection of the child; Public law; Turkey. Anayasa Mahkemesi; Türk Anayasa Mahkemesi; Türkiye. Anayasa Mahkemesi; United Nations Convention on the Rights of the Child